1995
DOI: 10.1093/humrep/10.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cytokines (interleukin-1, interleukin-6, transforming growth factor- ) and soluble tumour necrosis factor receptors in embryo culture fluids during in-vitro fertilization

Abstract: Several lines of evidence suggest that a number of immunoactive cytokines participate in early reproductive events such as implantation and placental development. Furthermore, cytokines may influence embryo growth and differentiation. In the present study, the production of tumour necrosis factor (TNF), interleukin-1 (IL1), interleukin-6 (IL6) and transforming growth factor-beta (TGF beta) during the first 48 h after oocyte retrieval during in-vitro fertilization was investigated. In addition, the question was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…Cytokines are of central importance for the regulation of inflammation, tissue remodeling, and embryogenic development [5,6]. Yet little is known about the local expression of pro-inflammatory cytokines in the cleft lip and palate tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines are of central importance for the regulation of inflammation, tissue remodeling, and embryogenic development [5,6]. Yet little is known about the local expression of pro-inflammatory cytokines in the cleft lip and palate tissues.…”
Section: Discussionmentioning
confidence: 99%
“…There are data about the cytokines role in the embryo growth and differentiation, as well as inflammation and the tissue remodeling [5,6]. Traditionally, these small, nonstructural proteins are subdivided into following families: interleukins, growth factors, chemokines, colony-stimulating factors, interferons, the transforming growth factor and the tumor necrosis factor families [7].…”
Section: Introductionmentioning
confidence: 99%
“…Huleihel et al [98] demonstrated that germ cells at different stages of development and differentiation may produce and release cytokines to regulate spermatogenesis in a paracrine or autocrine manner. Furthermore, Austgulen et al [99] suggest that sperm cells may be a source of cytokines production during embryo growth and implantation. These data suggest the presence of proteins involved in cytokines production in ejaculated sperm of subjects with Low DNA fragmentation.…”
Section: Enriched Functions In the Low Sperm Dna Fragmentation Groupmentioning
confidence: 99%
“…The maternal-fetal interaction stimulates proliferation and differentiation of trophoblasts and endometrial decidualization, which likely are spatially and temporally regulated by autocrine and paracrine systems [1,2]. Various cytokines and growth factors derived from the maternal endometrium and blastocysts, such as interleukin (IL)-1, IL-6, transforming growth factor ␤ (TGF␤), insulin-like growth factor (IGF), and tumor necrosis factor ␣ (TNF␣), have been associated with embryo development and implantation [3][4][5]. Moreover, an earlier study using knockout mice lacking the hepatocyte growth factor (HGF) gene has demonstrated that HGF is involved in placental growth and development [6].…”
Section: Introductionmentioning
confidence: 99%